2012
DOI: 10.1002/chem.201103651
|View full text |Cite
|
Sign up to set email alerts
|

Isolable Chiral Aggregates of Achiral π‐Conjugated Carboxylic Acids

Abstract: The induced aggregation of achiral building blocks by a chiral species to form chiral aggregates with memorized chirality has been observed for a number of systems. However, chiral memory in isolated aggregates of achiral building blocks remains rare. One possible reason for this discrepancy could be that not much is understood in terms of designing these chiral aggregates. Herein, we report a strategy for creating such isolable chiral aggregates from achiral building blocks that retain chiral memory after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Moreover, the signals seen in the IR spectra for the sam- ples obtained from batteries containing LiPF 6 do not match with LiPF 6 , POF 3 , [48] or H 3 PO 4 . 31 P NMR spectroscopy performed in D 2 O on the LP30 sample revealed multiple peaks at 1-2 ppm in the phosphate O = P(OR) 3 area and a single minor peak at 20 ppm in the phosphonate O = PR(OR') 2 area. This indicates that LiPF 6 /POF 3 are not present and underwent further evolution to water-stable phosphate/phosphonate derivatives.…”
Section: Extraction Of Bdali 2 From a Spent Batterymentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, the signals seen in the IR spectra for the sam- ples obtained from batteries containing LiPF 6 do not match with LiPF 6 , POF 3 , [48] or H 3 PO 4 . 31 P NMR spectroscopy performed in D 2 O on the LP30 sample revealed multiple peaks at 1-2 ppm in the phosphate O = P(OR) 3 area and a single minor peak at 20 ppm in the phosphonate O = PR(OR') 2 area. This indicates that LiPF 6 /POF 3 are not present and underwent further evolution to water-stable phosphate/phosphonate derivatives.…”
Section: Extraction Of Bdali 2 From a Spent Batterymentioning
confidence: 98%
“…[31] Malonic acid 2 is a natural but toxic compound that can be found in fermented fruits or fruit vinegars, [32] but it is especially abundant in alfalfa, [33] one of the most cultivated forage legumes in the world. For instance, dilithium trans-trans benzenediacrylate 1 could be synthesized through a Doebner modification of the Knoevenagel condensation from malonic acid 2 and terephthalaldehyde 3 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This exciton type CE is near to the absorption maximum of the aggregate suspension, indicating that the CE was due to the chiral interaction between the chromophores. Since the individual molecular building block is achiral, the strong bisignated CD signal, corresponding to the negative exciton-coupled CD, clearly indicates the presence of a helical arrangement of the transition dipoles that were polarized along the long axis of the azobenzene skeleton within a stack, 21 suggesting breaking of the chiral symmetry. The aggregate suspension had the same CD spectrum after being stored for several months, thus the racemization did not occur after the helical stacks had formed.…”
Section: Spectroscopymentioning
confidence: 99%
“…Simulations by Wang and Somasundaran 25 suggest that NaCMC adopts a helical conformation in bulk and in solution while Biermann et al 26 found that, depending on the substitution pattern, the chain may be locally collapsed or highly extended. Although a helical chain conformation is suggested by optical rotary dispersion and circular dichroism data, 27 29 light scattering, intrinsic viscosity, potentiometric titration, and dielectric spectroscopy data have been successfully interpreted assuming a locally linear conformation. 11 , 17 , 24 , 30 , 31 …”
Section: Introductionmentioning
confidence: 99%